Semi-automatic e-chartering through multi-agent systems and satellite IP networks. (25th September 2009) - Sardis, Manolis; Vouyioukas, Demosthenes; Anagnostopoulos, Ioannis
This paper proposes a semi-automatic e-chartering in maritime markets though distributed multi-agent infrastructure over satellite IP networks. Using a distributed Multi-Agent system for Internet Virtual Chartering Markets (MAVCM) in each maritime port and the satellite information from participating vessels, we propose a mechanism for semi-automatic control and creation of e-chartering contracts services. The MAVCM system applies for business-to-business transactions in maritime markets, and provides mechanisms for Internet-based chartering informational and transactional services. The proposed system is based on Shipowners and shippers maritime contracts through the MAVCM infrastructure, services and satellite monitoring of the vessels.